Review—Recent Advances in the Development of Porous Carbon-Based Electrocatalysts for Water-Splitting Reaction. Issue 5 (1st May 2022) - Chen, Tse-Wei; Kalimuthu, Palraj; Veerakumar, Pitchaimani; Chen, Shen-Ming; Anushya, Ganesan; Jeyapragasam, Tharini; Lin, King-Chen; Mariyappan, Vinitha; Ramachandran, Rasu
Abstract : The porous carbon-based materials (PCMs) have recently been attracted to many applications, specifically energy conversion and storage devices, due to their excellent electrocatalytic activities and abundant nature. The PCMs possess fascinating properties, including unique porosity, low cost, higher conductivity, fast mass transport for easy access of analytes and durability. Here, we have highlighted the different forms of PCMs, such as nanoporous, mesoporous, graphene, metal, and metal oxides based carbon composites for water-splitting reactions and their significance in important energy storage devices (metal-air batteries and fuel cells). This review is mainly focused on the various approaches for the preparation of porous carbon-based materials over the last ten years and the fabricated materials that could be applied in large-scale practical energy-related applications. In addition, we summarize the most promising strategies for the development of morphological structural based electrocatalysts to enhance their electrocatalytic performances for both OER and HER activities are discussed.